Optimisation of process parameters using D-optimal for enzymatic synthesis of polycaprolactone - Pakalapati, Harshini; Balaji, Anand B.; Senthil, K. Arumugasamy; Khalid, Mohammad * (Springer Verlag, 2017)
This work emphasizes on reactor scale synthesis of polycaprolactone using e-caprolactone as monomer and Candida antarctica lipase B enzyme as catalyst. The bio-polymerization was performed in 2 L thermostatic reactor by the conventional method with constant stirring. Optimisation of process parameters such as reactor temperature, reaction time, and mixing speed was carried out using response surface methodology based on D-optimal design. Molecular weight of the bio-polymer was chosen as the response for optimization, which is later characterised by gel permeation chromatography. The results show good agreement between predicted values and actual values obtained through the experiments.